2022
DOI: 10.3390/polym14122428
|View full text |Cite
|
Sign up to set email alerts
|

One-Pot Synthesis of UPy-Functionalized Nanocellulose under Mechanochemical Synergy for High-Performance Epoxy Nanocomposites

Abstract: The high strength, high specific surface area, excellent biocompatibility, and degradability of nanocellulose (NCC) make it a potential reinforcing phase for composite materials. However, the polyhydroxyl property of NCC renders it prone to self-aggregation and it has weak interfacial compatibility with non-polar substrates, limiting its enhancement performance for composite materials. Therefore, based on the high reactivity of NCC, the chemical modification of NCC to introduce functional groups is the basis f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Wang and co-workers 28 28 used ureido-pyrimidinone (UPy) to functionalize the nanocellulose (NC) surface to decrease self-aggregation and to improve the interfacial compatibility with the epoxy resin for the development of advanced nanocomposites. The morphological analysis revealed that the NC-UPy dispersed uniformly in the polymeric matrix, showing a good interfacial compatibility, leading to an 87% increase in the tensile strength of the formed nanocomposite membrane when the tensile strength of the composite material with 0.5 wt % NCC-UPy showed an 87% increase in comparison with the neat sample, thus demonstrating the outstanding reinforcing effect of the functionalized nanocellulose.…”
Section: Introductionmentioning
confidence: 99%
“…Wang and co-workers 28 28 used ureido-pyrimidinone (UPy) to functionalize the nanocellulose (NC) surface to decrease self-aggregation and to improve the interfacial compatibility with the epoxy resin for the development of advanced nanocomposites. The morphological analysis revealed that the NC-UPy dispersed uniformly in the polymeric matrix, showing a good interfacial compatibility, leading to an 87% increase in the tensile strength of the formed nanocomposite membrane when the tensile strength of the composite material with 0.5 wt % NCC-UPy showed an 87% increase in comparison with the neat sample, thus demonstrating the outstanding reinforcing effect of the functionalized nanocellulose.…”
Section: Introductionmentioning
confidence: 99%